Evaluation of histopathology of endometrium in primary infertile women, a prospective five years observational study in Konaseema region of Andhra Pradesh - P., Annapurna; Pattnaik, Niharika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Histopathology of endometrium is considered important investigation in case of infertility. The functional disturbance involved in infertility may result in morphological changes in endometrium. Endometrial histopathology is helpful in dating of endometrium so that hormonal status, ovulation and infertility. Methods: The material for this study consists of endometrial tissue obtained from patients. It was collected either by endometrial biopsy or curettage of uterus done in the minor OT department of obstetrics and gynaecology. The specimen was processed paraffin tissue processing and section of five micrometer was cut and stained with hematoxylin and eosin and ZN staining as per requirement. Results: Morphological and histopathological pattern of endometrium of patients with primary infertility, anovulatory (proliferative endometrium was present in 24 (30%) patients, simple hyperplasia was present in 16 (20%), deficient secretary phase was present in 26 (32.50%) patients, adequate secretary phase was present in 7 (8.75%) patients. Endometrial tuberculosis was diagnosed in 4 (5%) patients and in one patient neoplastic change was found. Arias Stella reaction was present in 1 (1.25%) patients. Conclusions: From present study we can conclude that the mean age of patients with primary infertility was 25.76±3.21 years and most of the patients were between 26 to 35 years of age. Regular menstrual cycle was present in 54 (67.5%) patients and 32.5% patients were presented with irregular cycle. The duration of infertility between 3 to 6 years was present in 34 (42.5%) patients. Secretory endometrium was present in 52.5% patients and was most common finding followed by proliferative endometrium. Endometrial tuberculosis was present in 2.5% patients.